Comparison of the Influence of Process Fluids on Tool Life in Face Milling - Jersák, Jan; Kaplan, František (Manufacturing Technology Journal, 2015)
Thanks to their chemical and mechanical properties, the process fluids (PFs) can significantly affect the process of machining [2], [15], [16], [18]. It is particularly important that PFs should positively influence the quality of the machined surfaces of machine parts and durability of cutting tools [4], [5], [6], [7], [10], [11], [12], [14]. Other significant factors in PFs are economic and environmental [17]. The costs of the acquisition, use and disposal of PFs must not be too high. As part of the research project in collaboration with the company Paramo, a.s. and the Technical University of Liberec, completely new environment-friendly PFs (labeled as PF01, PF02, PF03, PF04, and PF05) have been developed and evaluated. In the Laboratory of Machining at the Technical University of Liberec, the effects of these new PFs were examined from a viewpoint of a number of technological aspects. This article presents the results of experiments conducted on structural steel 16MnCr5 and stainless steel X2CrNiMo18-14-3 face milling using these newly developed eco-PFs.
Keywords: machining; milling; process fluid; environment-friendly; tool durability